The hope chest - Brown, Carolyn, 1948- (Montlake, 2021)
"An inheritance has reunited three estranged cousins. Their grandmother Lucy left Nessa, Flynn, and April her home nestled in the woods near Blossom, Texas, as well as a hope chest to be unlocked after they complete a special task. Together, they must hand-stitch a cherished quilt Lucy left unfinished. It meant everything to her. And now, to three people struggling with their own patchwork pasts... To Nessa, the house has always been an escape from her strict parents--a home away from home. Flynn has followed a profligate path into adulthood, never guessing it would lead him here. And the town of Blossom only stirs up a lifetime of disappointments for April. Lost and with nowhere to go, her last chance is helping fulfill Nanny Lucy's final wish. Thread by healing thread, Nessa, Flynn, and April bond over the quilt and all it represents. As they discover the family they've been looking for in one another, they share more than memories. They share the hope of new beginnings." -- Amazon.